2016
DOI: 10.1002/14651858.cd010836.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for treating ankle fractures in children

Abstract: There is low-quality evidence of a quicker recovery of self reported function at four weeks in children with clinically diagnosed low-risk ankle fractures who are treated with an ankle brace compared with those treated with a rigid cast, especially a non-removable walking cast. There is otherwise a lack of evidence from randomised controlled trials to inform clinical practice for children with ankle fractures. Research to identify and address priority questions on the treatment of these common fractures is nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…The regression model indicates that, if this trend continues, there will be about three times more low-trauma ankle fractures in Finland in the year 2030 than there was in 2000.³ In children ankle fractures occur in about 1 per 1000 per year. 4 , 5 Ankle fractures have a bimodal age distribution with peaks in younger males and older females.⁶ There has been three-fold increase in the incidence amongst elderly females over the past three decades.⁷ In addition, amongst multiply injured patients foot injuries are prognostically important: those who survive their injuries are far more impaired functionally if they have a foot injury in addition to multisystem trauma. 8 , 9 Ankle fractures result in significant morbidity in adults, with prognosis worsening with increasing age.¹⁰ They usually result from indirect traumas.…”
Section: Ethical Publication Statementsmentioning
confidence: 99%
“…The regression model indicates that, if this trend continues, there will be about three times more low-trauma ankle fractures in Finland in the year 2030 than there was in 2000.³ In children ankle fractures occur in about 1 per 1000 per year. 4 , 5 Ankle fractures have a bimodal age distribution with peaks in younger males and older females.⁶ There has been three-fold increase in the incidence amongst elderly females over the past three decades.⁷ In addition, amongst multiply injured patients foot injuries are prognostically important: those who survive their injuries are far more impaired functionally if they have a foot injury in addition to multisystem trauma. 8 , 9 Ankle fractures result in significant morbidity in adults, with prognosis worsening with increasing age.¹⁰ They usually result from indirect traumas.…”
Section: Ethical Publication Statementsmentioning
confidence: 99%
“…There are six Cochrane reviews that have evaluated the literature supporting the management of childhood fractures 3–8. The reviews have identified 45 trials with sufficient quality to inform practice, with most trials relating to the management of wrist fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The reviews have identified 45 trials with sufficient quality to inform practice, with most trials relating to the management of wrist fractures. Only two reviews were able to draw firm conclusions due to a paucity of randomised trials in children’s fracture care, despite the relative high frequency of these injuries 5 7…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is limited for the use of removable immobilization, such as Controlled Ankle Motion (CAM) boot, versus short leg walking casts (CAST) for these injuries. In the recent Cochrane reviews of Pediatric Ankle Fractures, 3 studies discussed removable immobilization versus plaster or fiberglass casting for these injuries 5–8 . All 3 studies concluded that removable immobilization is more effective and results in faster recovery of physical function, greater family and patient satisfaction, and is less costly than traditional casting 6–8 .…”
mentioning
confidence: 99%